QUALITY ASSESSMENT FOR SOME SACHET WATER PRODUCED IN ENUGU METROPOLIS, ENUGU–NIGERIA - CHIWETALU, UCHE; Nebechukwu, Agatha Chidinma; Attah, Onyinye Henrietta (FUDMA JOURNAL OF SCIENCES, 2022)
This study investigated the quality of some sachet water brands produced in Enugu metropolis for drinking purpose. Five different brands of sachet water were collected from their production plant and their physical, chemical and bacteriological qualities were examined. The results obtained for physical parameters showed that turbidity was 0 NTU; total dissolved solid was between 86.19 – 140.12 mg/L; total suspended solid, 0 mg/L; total solid 86.19 - 140.12 mg/L; electrical conductivity, 60.80 – 150.30 ms/cm3; total hardness, 0 mg/L; pH, 6.90 – 7.00 and alkalinity 50 mg/L. The result of the physical and chemical parameters conformed to the standards established by World Health Organization (WHO) and Nigeria standard for drinking water quality (NSDWQ). Similarly, biological contamination was absence in all the tested water samples. Thus, the examined sachet water brands were considered safe for consumption
Keywords: Assessment, Enugu, Metropolis, Quality, Sachet, Water